2022
DOI: 10.1093/ibd/izac174
|View full text |Cite
|
Sign up to set email alerts
|

Postvaccination Symptoms After a Third Dose of mRNA SARS-CoV-2 Vaccination in Patients With Inflammatory Bowel Disease: Results From CORALE-IBD

Abstract: Background The safety of a third dose of SARS-CoV-2 mRNA vaccination in patients with inflammatory bowel disease is unknown. Methods We compared symptoms following a third SARS-CoV-2 mRNA vaccine dose with symptoms after the second dose in IBD. Results The study group included 594 patients (70% female, 58% BNT162b2). Overall, 41% reported symptoms after a thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Booster vaccines were shown to be safe in IBD patients and several studies analysed booster vaccine-elicited immune responses in different subgroups of immunocompromised patients. [21][22][23][24][25][26][27] However, to our knowledge, this is the first study to when comparing them to IBD patients without immunosuppressive treatment. [24][25][26][28][29][30] Importantly, it must be noted that the reduced antibody responses found in this study, might at least partially be influenced by already reduced antibody concentrations in anti-TNFtreated patients after two vaccine doses as shown before.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Booster vaccines were shown to be safe in IBD patients and several studies analysed booster vaccine-elicited immune responses in different subgroups of immunocompromised patients. [21][22][23][24][25][26][27] However, to our knowledge, this is the first study to when comparing them to IBD patients without immunosuppressive treatment. [24][25][26][28][29][30] Importantly, it must be noted that the reduced antibody responses found in this study, might at least partially be influenced by already reduced antibody concentrations in anti-TNFtreated patients after two vaccine doses as shown before.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, vaccination campaigns worldwide recommend a SARS‐CoV‐2 booster vaccine for immunosuppressed patients. Booster vaccines were shown to be safe in IBD patients and several studies analysed booster vaccine‐elicited immune responses in different subgroups of immunocompromised patients 21–27 . However, to our knowledge, this is the first study to prospectively characterise the humoral and functional cellular immune responses following a third dose with SARS‐CoV‐2 mRNA vaccines in IBD patients receiving immunosuppressive treatment and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…52 As in the PREVENT-COVID cohort, severe reactions after the third dose were less common than after the second. 53…”
Section: Safetymentioning
confidence: 99%
“…52 As in the PREVENT-COVID cohort, severe reactions after the third dose were less common than after the second. 53 Data from up to 30 days post vaccination has also been reassuring. Hadi et al identified 5562 patients with IBD who received a COVID-19 vaccine and found no difference in adverse events as compared to a propensity score matched population without IBD who received the COVID-19 vaccine.…”
Section: Safetymentioning
confidence: 99%
“…Overall, the short-term adverse events to SARS-CoV-2 vaccines in those with IBD are similar to the general population. A cohort study from the US showed that the most commonly reported adverse events after receiving a vaccine were: injection site pain, fatigue, and malaise; the rate of reporting in those with IBD was not different than healthy controls ( 40 ). Adverse events were classified as mild and short-lived (i.e., less than two days).…”
Section: Introduction: Crohn’s and Colitis Canada’s Covid-19 And Ibd ...mentioning
confidence: 99%